2021
DOI: 10.1111/sode.12549
|View full text |Cite
|
Sign up to set email alerts
|

Emotion matters in early polite lies: Preschoolers’ polite lie‐telling in relation to cognitive and emotion‐related abilities

Abstract: Most prior studies on children's polite lie-telling have focused on cognitive correlates but neglected emotional correlates. This study examined 115 preschoolers' polite lie-telling in relation to both cognitive (inhibitory control (IC), false-belief understanding) and emotion-related abilities (emotional theory of mind (ToM), affective empathy).After receiving a disappointing gift, 53 (46.1%) preschoolers lied. Preschoolers' polite lie-telling was positively related to their emotional ToM but not to IC, false… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Moreover, in some contexts, that is, in politeness settings, people tend to both hide their emotions and lie (Cole, 1986;Talwar & Lee, 2002). In line with this, Wang et al (2022) indicated that children with more advanced emotional ToM -hidden emotion understanding and understanding of emotions that follow a false belief -are more likely to praise a gift-giver falsely. Deceiving a potential aggressor children should also control their emotional expression, sometimes even hide their true feelings.…”
Section: Interventional Deception As a Prosocial Actionmentioning
confidence: 70%
“…Moreover, in some contexts, that is, in politeness settings, people tend to both hide their emotions and lie (Cole, 1986;Talwar & Lee, 2002). In line with this, Wang et al (2022) indicated that children with more advanced emotional ToM -hidden emotion understanding and understanding of emotions that follow a false belief -are more likely to praise a gift-giver falsely. Deceiving a potential aggressor children should also control their emotional expression, sometimes even hide their true feelings.…”
Section: Interventional Deception As a Prosocial Actionmentioning
confidence: 70%
“…Thus, in many papers, the principal research question was focused either on the mutual impact of EFs and ToM on other social or cognitive skills (e.g., sharing, general cognitive development) or on the contribution of some other cognitive mechanisms (e.g., phonological awareness) on EFs and ToM performance. Among those cases, 45 papers, after being carefully evaluated, were excluded for reporting results exclusively on the relationship of ToM with the third involved variable and not providing data on the relationship between ToM and EFs (e.g., Demetriou et al, 2021;Matthews et al, 2018;Liu et al, 2016;Venkadasalam et al, 2022;Wang et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In the paradigm, children receive a gift they do not like after completing a game with the experimenter, and then the experimenter asks the children if they like the gift. Results consistently show that children as young as 3–4 years old are able to tell polite lies to the experimenter by stating they like the gift (while telling their parents that they do not like the gift) [ 4 , 9 , 10 , 11 , 12 , 13 , 14 ]. As age increases, children tend to tell more polite lies (but also see [ 10 ]) and their lying behavior becomes more sophisticated.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies using similar paradigms did not find a significant relation between children’s polite lying behavior and their ToM performances. For example, Wang et al [ 12 ] found that preschoolers’ polite lying was not significantly related to their ToM performances (also see [ 17 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation